1991
DOI: 10.1507/endocrj1954.38.597
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Sulfatase Activities in Human Leukocytes: Biochemical and Clinical Aspects.

Abstract: Abstract. Steroid sulfatase is a membrane-bound microsomal enzyme, present in various tissues. In this report, data on sulfatase activity in peripheral blood leukocytes isolated from normal women and the characterization of its enzyme are studied. In addition, sulfatase activities in placental sulfatase deficiency (PSD) and ichthyosis patients including ichthyosis vulgaris (IV) and recessive X-linked ichthyosis (RXLI) were analysed and were compared with normal subjects. Steroid sulfatase activity was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The effects of DHEA might not be exerted via DHEA-specific receptors, but rather via receptors for active androgenic metabolites of DHEA-S and DHEA generated in immune cells (44). Specifically leukocytes, including macrophages, possess the sulphatases and other enzymes important in this conversion (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of DHEA might not be exerted via DHEA-specific receptors, but rather via receptors for active androgenic metabolites of DHEA-S and DHEA generated in immune cells (44). Specifically leukocytes, including macrophages, possess the sulphatases and other enzymes important in this conversion (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the high levels of progesterone present during the luteal phase may be involved in regulating STS activity. STS activity in PBLs obtained from men is lower than that in cells from female subjects (26,180). Because many breast tumors are infiltrated by macrophages and lymphocytes (181), it is possible that the STS activity of these cells may make an important contribution to estrogen synthesis within tumors.…”
Section: G Sts Activity In Leukocytes and Thrombocytesmentioning
confidence: 99%
“…In 1978, Shapiro et al (2,3) demonstrated the steroid sulfatase (STS) deficiency in X-linked ichthyosis (XLI). Since then, several clinical features have been proposed to distinguish among the types, especially between XLI and ichthyosis vulgaris (IV), as both types appear at a high frequency (4)(5)(6). IV shows fine, white and irregular scales; the extremities are usually more involved than the trunk.…”
Section: Introductionmentioning
confidence: 99%